A method of making a composite material for non-stick cookware

By covering the tough metal layer on the surface of the perovskite material, the problems of poor uniformity and insufficient non-stickness of metal-ceramic composite materials are solved, high hardness, high stability and high temperature resistance are achieved, and the service life of non-stick cookware is extended .

CN115522179BActive Publication Date: 2025-01-03WUHAN SUPOR COOKWARE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211211023.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-01-03
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

Existing metal-ceramic composites have poor uniformity and insufficient non-stickness in non-stick cooking utensils, resulting in short non-stick life.

Method used

By fluidizing the perovskite material and covering the surface of it with a tough metal layer, a reductive gas reacts with the precursor to form a tough metal layer, thereby improving the uniformity and non-stickness of the composite material.

Benefits of technology

It realizes the high hardness, high stability and high temperature resistance of composite materials, extends the service life of non-stick cookware, and improves the wear resistance and scratch resistance of non-stick coatings.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a composite material for non-stick cookware. The method comprises: fluidizing a perovskite material with a reducing gas to form a perovskite material in a fluidized state; and reacting a precursor containing a ductile metal with a reducing gas to reduce the precursor to a ductile metal, thereby coating the surface of the perovskite material with a ductile metal layer, wherein the precursor comprises at least one of an alkyl ductile metal and a carbonyl ductile metal, wherein the perovskite material is represented by ABO3, A comprises at least one of an alkaline earth metal, and B comprises at least one of a transition metal, wherein the ductile metal comprises a ductile metal having an elongation at break greater than or equal to 12%. According to an embodiment of the present invention, the problem of poor uniformity and insufficient non-stickiness of metal-ceramic composite materials in the prior art can be solved by the atomic deposition method according to the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of non-stick cookware, and more particularly to a method for manufacturing a composite material for non-stick cookware. Background Art

[0002] Existing non-stick cookware products mainly spray a layer of fluororesin coating on the surface of the metal substrate to achieve the non-stick effect. However, the current fluororesin products have the problem of short non-stick life. With the development of technology, metal-ceramic powder type non-stick cookware has emerged, but metal-ceramic powder has the problem of poor uniformity in the form of mixing or granulation, and ordinary coating technology is prone to agglomeration for micro-nano-level particle powders, resulting in uneven composition and affecting non-stick properties.

[0003] Therefore, there is a need to develop a new method for manufacturing composite materials for non-stick cookware. Summary of the invention

[0004] The present invention aims to solve the above technical problems in the related art. To this end, the purpose of the present invention is to provide a method for manufacturing a composite material for non-stick cookware, thereby solving the problems of poor uniformity and insufficient non-stickiness of metal-ceramic composite materials in the prior art.

[0005] According to aspects of the present invention, a method for manufacturing a composite material for non-stick cookware is provided, the method comprising the following steps: fluidizing a perovskite material with a reducing gas to form a perovskite material in a fluidized state; and reacting a precursor containing a ductile metal with the reducing gas to reduce the precursor to a ductile metal, thereby coating the surface of the perovskite material with a ductile metal layer, wherein the precursor comprises at least one of an alkyl ductile metal and a carbonyl ductile metal, wherein the perovskite material is represented by ABO3, A comprises at least one of an alkaline earth metal, and B comprises at least one of a transition metal, wherein the ductile metal comprises a ductile metal having an elongation at break greater than or equal to 12%. This method can solve the problems of poor uniformity and insufficient non-stickiness of metal-ceramic composite materials in the prior art.

[0006] According to an embodiment of the present invention, A may be Ca, and B may be Ti. By including a predetermined perovskite material, the composite material may have properties such as high hardness, high stability, and good high temperature resistance.

[0007] According to an embodiment of the present invention, the ductile metal may include Fe, Al, Cu, Ni or alloys thereof. By using a predetermined ductile metal material, the hardness of the composite material may be improved.

[0008] According to an embodiment of the present invention, the perovskite material may be in the form of particles, and the average particle size of the perovskite material in the form of particles may be 10 μm to 100 μm. By controlling the particle size of the perovskite material, the composite material may have properties such as high hardness and high stability.

[0009] According to an embodiment of the present invention, the step of fluidizing the perovskite material may be performed at a fluidization rate of 0.8 m / s to 2 m / s and a fluidization temperature of 150° C. to 400° C. Performing fluidization under such conditions can further ensure the dispersibility of the perovskite material.

[0010] According to an embodiment of the present invention, the reducing gas may include hydrogen, and the precursor may include at least one of C1 to C10 alkyl aluminum and C1 to C10 alkyl nickel. By using such a precursor, the formation of a ductile metal layer can be ensured.

[0011] According to an embodiment of the present invention, the precursor may include at least one of trimethylaluminum, diethylnickel, carbonyl copper and carbonyl iron. By using such a precursor, the formation of a ductile metal layer can be ensured.

[0012] According to an embodiment of the present invention, in the step of reacting the precursor containing the ductile metal with the reducing gas, the precursor containing the ductile metal is atomized by an inert gas to react the precursor containing the ductile metal with the reducing gas. This step can ensure that a ductile metal layer of a desired thickness is formed.

[0013] According to an embodiment of the present invention, the method may further include: after the step of reacting the precursor containing the ductile metal with the reducing gas, removing excess precursor with an inert gas. This step can ensure the formation of a ductile metal layer of a desired thickness.

[0014] According to an embodiment of the present invention, the thickness of the ductile metal layer may be 0.1 μm to 5 μm. By controlling the thickness of the ductile metal layer, the non-stick cookware may have properties such as high hardness and high stability.

[0015] According to the embodiments of the present invention, the problems of poor uniformity and insufficient non-stickiness of metal-ceramic composite materials in the prior art can be solved by the atomic deposition method according to the present invention. In addition, the non-stick cookware including the composite material prepared by the method according to the present invention has properties such as high hardness, high wear resistance, high temperature resistance and improved life, achieving a non-stick effect. DETAILED DESCRIPTION

[0016] Embodiments of the present invention will be described in more detail below. Although exemplary embodiments of the present invention are described hereinafter, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0017] The present invention forms a composite material with a non-stick effect by coating a ductile metal on the surface of a perovskite material through an atomic deposition technique. The composite material is formed on a non-stick cookware through a thermal spraying process or a cold spraying process to form a non-stick coating with both a non-stick effect and wear resistance and scratch resistance, thereby solving the problems existing in fluororesins in the field of existing non-stick materials.

[0018] Hereinafter, a method for manufacturing a composite material for non-stick cookware according to the present invention will be described in detail.

[0019] The method for manufacturing a composite material for non-stick cookware of the present invention comprises the following steps: fluidizing a perovskite material with a reducing gas to form a perovskite material in a fluidized state; and reacting a precursor containing a ductile metal with the reducing gas to reduce the precursor to a ductile metal, thereby coating the surface of the perovskite material with a ductile metal layer.

[0020] In the step of fluidizing the perovskite material with a reducing gas, the perovskite material is fluidized using a fluidized bed to form a perovskite material in a fluidized state. Specifically, a perovskite material in the form of particles (e.g., with an average particle size of 10 μm to 100 μm) can be placed in a chamber of a fluidized bed, and then the perovskite material is suspended under the action of a reducing gas at a fluidization rate of 0.8 m / s to 2 m / s and a fluidization temperature of 150° C. to 400° C., thereby obtaining a perovskite material in a fluidized state.

[0021] In an embodiment of the present invention, the average particle size of the perovskite material may be 10 μm to 90 μm, 10 μm to 80 μm, 10 μm to 70 μm, 10 μm to 60 μm, 10 μm to 50 μm, 10 μm to 40 μm, 10 μm to 30 μm, 10 μm to 20 μm, 20 μm to 90 μm, 20 μm to 80 μm, 20 μm to 70 μm, 20 μm to 60 μm, 20 μm to 50 μm, 20 μm to 40 μm, 20 μm to 30 μm, 30 μm to 90 μm, 30 μm to 80 μm , 30μm to 70μm, 30μm to 60μm, 30μm to 50μm, 30μm to 40μm, 40μm to 90μm, 40μm to 80μm, 40μm to 70μm, 40μm to 60μm, 40μm to 50μm, 50μm to 90μm, 50μm to 80μm, 50μm to 70μm, 50μm to 60μm, 60μm to 90μm, 60μm to 80μm, 60μm to 70μm, 70μm to 90μm, 70μm to 80μm, 80μm to 90μm, etc. Specifically, the average particle size of the perovskite material can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, etc.

[0022] The perovskite material is represented by ABO3, wherein A includes at least one of alkaline earth metals and B includes at least one of transition metals.

[0023] For example, A may include at least one of Ca and Mg, and preferably, A may be Ca. B may include at least one of Ti, Mn and Co, and preferably, A may be Ti. That is, the perovskite material may be a calcium titanate ceramic material.

[0024] Perovskite materials (specifically, calcium titanate ceramic materials) have special properties. Specifically, perovskite materials can have a typical ABX3 crystal structure. As a representative of perovskite materials, calcium titanate 113 structure can have a large number of oxygen vacancies and crystal defects. In the ABX3 crystal structure of perovskite materials, the A position can be a Ca metal cation, and the B position can be a Ti metal cation. When heated, the metal cations at the A position and the B position will be displaced to cause lattice distortion, reduce the symmetry and order of the crystal structure, and reduce the surface energy, thereby showing a certain non-stick effect. In detail, as the most typical representative of perovskite materials, calcium titanate is currently commonly used in the photovoltaic industry and has excellent photoelectric conversion efficiency. Calcium titanate belongs to the cubic system. Since calcium titanate crystals are easily distorted by TiO6 rotation or cation displacement, thereby reducing the symmetry of the crystal structure, calcium titanate often undergoes phase transitions between cubic, tetragonal and orthorhombic systems. During the lattice distortion of calcium titanate, the orderliness of the material's crystal structure decreases and the surface free energy decreases, so calcium titanate can exhibit a certain degree of non-stickiness, and the magnitude of the non-stickiness can be related to the degree of lattice distortion of calcium titanate. Therefore, perovskite materials can be used as composite materials for non-stick cookware. Mixing perovskite materials with tough metal materials to prepare composite materials can further compensate for the problem of insufficient toughness of perovskite materials, thereby further increasing the non-stickiness of the composite materials.

[0025] In the step of reacting the precursor containing the ductile metal with the reducing gas, the precursor containing the ductile metal is reacted with the reducing gas to reduce the precursor to the ductile metal, so that the surface of the perovskite material is coated with a ductile metal layer. Specifically, the precursor containing the ductile metal is atomized by an inert gas (for example, argon or nitrogen) to react the precursor containing the ductile metal with the reducing gas to reduce the precursor to the ductile metal, so that the surface of the perovskite material is coated with a ductile metal layer.

[0026] In the embodiment of the present invention, the reducing gas and the precursor may be introduced continuously, and the atomized precursor may be introduced in a state where the reducing gas is in excess.

[0027] In an embodiment of the present invention, the reducing gas may include hydrogen, and the precursor may include at least one of a liquid alkyl ductile metal and a carbon-based ductile metal.

[0028] The alkyl ductile metal may include at least one of C1 to C10 alkyl aluminum and C1 to C10 alkyl nickel, and the carbon-based ductile metal may include at least one of carbonyl copper and carbonyl iron. Specifically, the ductile metal may include at least one of trimethyl aluminum, diethyl nickel, carbonyl copper and carbonyl iron.

[0029] In an embodiment of the present invention, after the step of reacting the precursor containing the ductile metal with the reducing gas, the excess precursor may be removed by using an inert gas. However, the present invention is not limited thereto, and this step may be omitted.

[0030] In an embodiment of the present invention, the thickness of the ductile metal layer obtained by each deposition may be 0.1 μm to 0.3 μm, and the ductile metal layer of desired thickness may be obtained by controlling the number of depositions; however, the present invention is not limited thereto. For example, the thickness of the ductile metal layer may be 0.1 μm to 5 μm (e.g., 0.5 μm to 1.5 μm).

[0031] In addition, the ductile metal layer may include a ductile metal having a fracture elongation greater than or equal to 12% and less than or equal to 20%, for example, Fe, Al, Cu, Ni, or an alloy thereof.

[0032] In an embodiment of the present invention, the elongation at break of the ductile metal material may be greater than or equal to about 12% and less than or equal to 20%. For example, the elongation at break of the ductile metal material may be greater than or equal to about 13%, greater than or equal to about 14%, greater than or equal to about 15%, greater than or equal to about 16%, greater than or equal to about 17%, greater than or equal to about 18%, or greater than or equal to about 19% and less than or equal to about 20%, etc. Specifically, the elongation at break of the ductile metal may be 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.

[0033] In an embodiment of the present invention, the weight ratio of the perovskite material to the precursor (eg, trimethylaluminum) may be controlled within a range of 4:3 to 1:3.

[0034] In the composite material manufactured by the method of the present invention, the composite material may include about 50wt%-80wt% of perovskite material and about 20wt%-50wt% of ductile metal based on the total weight of the composite material. If the perovskite material accounts for less than 50wt%, the non-stick effect is not obvious; if the perovskite material accounts for more than 80wt%, the non-stick coating is too brittle, and the accumulation of thermal stress during the spraying process easily causes the non-stick coating to collapse. If the ductile metal accounts for less than 20wt%, the composite material is not completely coated, and the non-stick coating formed subsequently is highly brittle; if the ductile metal accounts for more than 50wt%, the non-stick property of the composite material is affected.

[0035] In an embodiment of the present invention, compared with the prior art, the present invention innovatively uses perovskite materials (such as calcium titanate) as non-stick materials, and combines them with ductile metal materials to form a composite material to make up for its lack of toughness. And when the perovskite material is heated, the symmetry of its crystal structure will decrease, the surface energy will decrease, and the non-stickiness will increase, which is very suitable for kitchen cooking scenarios. In addition, the present invention uses atomic deposition coating means to evenly coat each small particle of perovskite material with a layer of ductile metal to obtain a composite material with uniform composition.

[0036] In addition, in the embodiments of the present invention, the method of the present invention can solve the problems of poor uniformity and insufficient non-stickiness of the metal-ceramic composite material in the prior art.

[0037] The method for manufacturing the composite material for non-stick cookware of the present invention will be described in detail below with reference to examples and comparative examples.

[0038] Example 1

[0039] In the chamber of the fluidized bed, calcium titanate powder with an average particle size of 50 μm is fluidized using hydrogen in an excess state, with a fluidization rate of 1.5 m / s and a fluidization temperature of 200° C.;

[0040] Trimethylaluminum is atomized by argon gas and then introduced into the chamber of the fluidized bed. The atomized trimethylaluminum contacts hydrogen gas to be reduced to aluminum, thereby coating the surface of the calcium titanate powder with an aluminum layer with a thickness of 0.5 μm, wherein the weight ratio of the calcium titanate powder to the trimethylaluminum is 4:3.

[0041] A plasma spraying process is used to form a non-stick coating on the aluminum alloy pot embryo. The specific parameters are as follows: the flow rate of the argon supply is 1500L / H; the flow rate of the hydrogen supply is 100L / H; the voltage is 50V; the current is 500A; the rate of feeding the composite material is 30g / min; the diameter of the straight hole gun nozzle is 25mm; and the distance between the spray gun and the pot embryo is 80mm.

[0042] The average thickness of the non-stick coating finally formed by the above steps is 50 μm.

[0043] Example 2

[0044] The difference from Example 1 is that an aluminum film with a thickness of 0.1 μm is formed on the surface of calcium titanate.

[0045] Example 3

[0046] The difference from Example 1 is that an aluminum film with a thickness of 5 μm is formed on the surface of calcium titanate.

[0047] Comparative Example 1

[0048] Titanium aluminum alloy powder and calcium titanate powder are directly mixed and then thermally sprayed to prepare a non-stick coating. Specifically, calcium titanate powder with an average particle size of 20 μm and FeTi with an average particle size of 20 μm are mixed. 30 The alloy powders are uniformly mixed in a mass ratio of 4:1 to obtain a composite material. Then, the composite material is preheated and sprayed on the aluminum alloy pot blank via a plasma spraying process after preheating.

[0049] In the plasma spraying process, the specific parameters are as follows: the flow rate of argon supply is 1500L / H; the flow rate of hydrogen supply is 100L / H; the voltage is 50V; the current is 500A; the rate of feeding the composite material is 30g / min; the diameter of the straight hole gun nozzle is 25mm; and the distance between the spray gun and the pot embryo is 80mm.

[0050] The average thickness of the non-stick coating finally formed by the above steps is 50 μm.

[0051] Comparative Example 2

[0052] The non-stick coating is prepared by granulating titanium aluminum alloy powder and calcium titanate powder and then thermally spraying. Specifically,

[0053] The calcium titanate powder material with an average particle size of 20 μm and the FeTi with an average particle size of 20 μm are used. 30 The alloy powders are mixed evenly, with the mass ratio of the two powders being 4:1; the mixed powders are preheated before plasma spraying. The purpose of preheating is to improve the powder fluidity and prevent gun clogging;

[0054] Adding a binder (hydroxypropyl methylcellulose), a dispersant (citric acid), and a defoamer (silicone oil) into deionized water to prepare a slurry comprising 2 wt % of the binder, 1 wt % of the dispersant, 2 wt % of the defoamer, and the balance of water;

[0055] After the slurry is prepared, the calcium titanate powder material and FeTi 30 The powder is added to the slurry to form a slurry with a solid content of 50 wt%;

[0056] The prepared slurry is transported to the high-speed liquid-spinning disc to form droplets, and then the droplets are blown into the drying tower by hot air. The droplets stay for a short time during the descent process and finally form granulated powder. The speed of the high-speed liquid-spinning disc can be controlled within the range of 8000 rpm. The temperature of the hot air can be controlled within the range of 80°C, the temperature of the drying tower can be controlled within the range of 300°C, and the short residence time of the droplets in the drying tower can be controlled to 10 seconds;

[0057] After spray drying, particles can be obtained. In order to remove the moisture present therein, the particles are sintered. The initial sintering temperature can be 25°C, the heating rate can be 5°C / min, the final temperature can be 150°C, and then the temperature can be kept for 5 hours;

[0058] The spraying substrate is an aluminum alloy pot embryo, and the pot embryo is sandblasted with 40-60 mesh brown corundum to make the roughness (Rz) of the pot embryo be 30-50μm; the composite material is plasma sprayed under the conditions of an argon supply flow rate of 1500L / H, a hydrogen supply flow rate of 100L / H, a voltage of 50V, a current of 500A, a rate of feeding the composite material of 30g / min, a nozzle diameter of 5mm, and a distance of 80mm from the spray gun to the pot embryo to form a non-stick coating with an average thickness of 50μm.

[0059] After plasma spraying, the non-stick coating is sanded to obtain a non-stick cooker with a smooth inner surface (ie, roughness Ra=4-8 μm, Rz=20-30 μm).

[0060] Testing the performance of non-stick cookware

[0061] The effects of Examples 1 to 3 and Comparative Examples 1 and 2 were tested using an accelerated simulation test and a persistent non-stick test. The specific test method is as follows:

[0062] Accelerated simulation (non-stick life) test

[0063] Referring to the accelerated simulation test procedure for non-stick frying pans, the non-stick life of the non-stick cookware prepared in Examples 1 to 3 and Comparative Examples 1 and 2 was evaluated, and the test process is as follows:

[0064] The non-stick cookware prepared in Examples 1 to 3 and Comparative Examples 1 and 2 was subjected to vibration wear resistance test, dry-fried mixed sauce test, boiling salt water test, quartz stone (shovel) test and fried egg non-stick rating test in sequence. When all the above test steps are completed, a test cycle is marked as finished.

[0065] In the vibration wear test , the specific parameters are as follows:

[0066] Instrument: Vibration wear tester.

[0067] Test method: 1) Place 1 kg of quartz stone (particle size 9 mm to 12 mm) into the non-stick cookware; 2) Place the non-stick cookware on a heating stove; 3) Set the instrument's vibration time to 15 minutes, the heating temperature to 150°C to 180°C, and the speed to 300 revolutions per minute; 4) Turn on the vibration button to vibrate the quartz stone inside the non-stick cookware for 15 minutes; and 5) After the test, pour out the quartz stone from the non-stick cookware, clean the inner surface of the non-stick cookware with detergent, and wipe it dry.

[0068] Quartz stone replacement cycle: once a month.

[0069] In the dry-fried mixed sauce test , the specific parameters are as follows:

[0070] Ingredients: soy sauce, vinegar, cooking wine, MSG, salt, sugar, cooking oil.

[0071] Test procedure and steps: 1) Prepare a mixed sauce according to the following weight ratio: soy sauce: vinegar: cooking wine: monosodium glutamate: salt: sugar: cooking oil = 4:3:2:1:1:2:2 (mass ratio) to completely dissolve all ingredients, mix them evenly and prepare a special mixed sauce; 2) Put 50g of the mixed sauce into a non-stick cookware, shake the non-stick cookware until the sauce evenly covers the bottom of the non-stick cookware; 3) Place the non-stick cookware on a gas stove and dry-heat it to 250°C to 270°C and keep it warm for 2 minutes, then stop heating; and 4) Rinse the non-stick cookware with water, and then wipe the contaminated area inside the non-stick cookware with detergent and a rag.

[0072] In the boiling salt water test , the specific parameters are as follows:

[0073] Ingredients: 50g salt, 950g water.

[0074] Test procedure and steps: 1) Weigh 50g of salt and 950g of water to prepare a 5wt% salt solution, and pour the salt solution into the non-stick cookware; 2) Start timing after the water boils, keep it slightly boiling for 10 minutes, and add water as needed to keep the concentration constant; and 3) After boiling for the specified time, use tap water to clean the non-stick cookware and wipe it dry.

[0075] In the test of fried quartz stone (shovel) , the specific parameters are as follows:

[0076] Ingredients: 1 kg of quartz stone with a particle size of 9 mm to 12 mm, oil, vinegar, cooking wine, soy sauce, and a little salt.

[0077] Test procedures and steps: 1) Pour 15g of cooking oil into the non-stick cookware, shake it evenly until the entire inner surface is soaked, heat it until oil smoke is produced, then pour 1Kg of quartz stone into the non-stick cookware, add a small amount of vinegar, cooking wine, soy sauce, water, and salt, and stir-fry evenly for 10 minutes; 2) After the end, use detergent to clean the inner surface of the non-stick cookware and wipe it dry; and 3) After each cycle, filter the soup and leave the quartz stone for the next cycle.

[0078] Quartz stone replacement cycle: once a month

[0079] During the accelerated simulation test, the non-stick life of the non-stick cookware is determined after each cycle. The test endpoint is determined when the non-stick cookware exhibits any of the following phenomena: (1) non-stick performance decreases: the non-stick rating of a fried egg is graded as Grade III for two consecutive cycles; and (2) appearance damage: the coating becomes fuzzy; the coating peeling area is larger than 3 mm in diameter 2 ; The substrate is obviously exposed due to wear; there are more than 3 puncture scratches on the coating (exposing the substrate); or there is dirt that cannot be washed off with a wet cloth.

[0080] The number of accelerated simulation test cycles recorded at the end of the test is the non-stick life of the non-stick cookware. The more cycles, the longer the non-stick life of the non-stick coating of the non-stick cookware. Generally speaking, a test is qualified if the number of cycles is greater than or equal to 3.

[0081] Long-lasting non-stick test method

[0082] With reference to the 5.6.9 long-lasting non-stick test method in the national standard GB / T32388-2015, the long-lasting non-stick properties of the non-stick cookware prepared in Examples 1 to 3 and Comparative Examples 1 and 2 were evaluated.

[0083] The test results of the non-stick life and the long-lasting non-stick property of the non-stick cookware prepared in Examples 1 to 3 and Comparative Examples 1 and 2 are shown in Table 1.

[0084] Table 1

[0085] sample Non-stick LNE Life Long-lasting non-stick life Comparative Example 1 Ⅱ 2 8000 Comparative Example 2 Ⅱ 1 2000 Example 1 Ⅰ 15 28000 Example 2 Ⅰ 10 18000 Example 3 Ⅱ 7 12000

[0086] Generally speaking, when the LNE life of the non-stick coating is greater than or equal to 5, and the long-lasting non-stick life of the non-stick coating is greater than or equal to 10,000, the non-stick cookware can be considered to have improved non-stick performance.

[0087] It can be seen from the data in Table 1 that, compared with Comparative Examples 1 and 2, the non-stick coatings of Examples 1 to 3 according to the present invention have improved non-stick properties, LNE life and long-lasting non-stick life.

[0088] In summary, according to the embodiments of the present invention, the composite material obtained by the method of the present invention can improve the non-stick property, LNE life and long-lasting non-stick life of the non-stick coating.

[0089] Although the present invention has been specifically shown and described with reference to the embodiments of the present invention, it will be understood by those skilled in the art that various changes in form and detail may be made herein without departing from the spirit and scope of the present invention as defined by the claims and their equivalents. The embodiments should be considered in a descriptive sense only and not for the purpose of limitation. Therefore, the scope of the present invention is not limited by the specific embodiments of the present invention, but by the claims, and all differences within the scope will be interpreted as included in the present invention.

Claims

1. A method for manufacturing a composite material for non-stick cookware, characterized in that The method comprises the following steps: Fluidizing the perovskite material using a reducing gas to form the perovskite material in a fluidized state; and reacting a precursor containing a ductile metal with a reducing gas to reduce the precursor to a ductile metal, thereby coating a surface of the perovskite material with a ductile metal layer, The precursor includes at least one of a liquid alkyl toughness metal and a liquid carbonyl toughness metal. Wherein, the perovskite material is represented by ABO3, A includes at least one of alkaline earth metals, B includes at least one of transition metals, Wherein, ductile metals include ductile metals having a fracture elongation greater than or equal to 12%. The alkyl ductile metal includes at least one of C1 to C10 alkyl aluminum and C1 to C10 alkyl nickel, and the carbon-based ductile metal includes at least one of carbonyl copper and carbonyl iron. Among them, A is Ca, B is Ti, The perovskite material is in the form of particles, and the average particle size of the perovskite material in the form of particles is 10 μm to 100 μm.

2. The method according to claim 1, characterized in that Ductile metals include Fe, Al, Cu, Ni or alloys thereof.

3. The method according to claim 1, characterized in that The step of fluidizing the perovskite material is performed under the conditions of a fluidization rate of 0.8 m / s to 2 m / s and a fluidization temperature of 150° C. to 400° C.

4. The method according to claim 1, characterized in that: Reducing gases include hydrogen.

5. The method according to claim 1, characterized in that: The precursor includes at least one of trimethylaluminum, diethylnickel, copper carbonyl and iron carbonyl.

6. The method according to claim 1, characterized in that In the step of reacting the precursor containing the ductile metal with the reducing gas, the precursor containing the ductile metal is atomized by the inert gas to react the precursor containing the ductile metal with the reducing gas.

7. The method according to claim 1, characterized in that The method further includes removing excess precursor using an inert gas after reacting the precursor containing the ductile metal with the reducing gas.

8. The method according to claim 1, characterized in that: The thickness of the ductile metal layer is 0.1 μm to 5 μm.